Influence of different combinations of speed and slope during running on heart rate variability - ElDash, Vivian (2019)
Every runner faces changes in speed and slope while exercising. While running faster or on a steepier surface represent different stimuli, both conditions lead to an increase in metabolic demand and therefore in heart rate (HR). The control of HR is given by both neural and non-neural components and can be accessed analyzing the heart rate variability (HRV). During exercise, HRV is known to be influenced by both sympathetic and parasympathetic branches of the autonomic nervous system, by breathing frequency, cadence, amongst other components. Hence, the present study sought to address how changes in speed and slope during running impact HR and HRV and whether the patterns observed for a restricted population were applicable to a broader group. We collected ECG records from volunteers divided into 2 groups: Experiment 1 (N = 12, with a broader range of ages and fitness level) and Experiment 2 (N = 9, composed of a more homogeneous population). Subjects ran on 9 (Experiment 1) or 16 (Experiment 2) combinations of speed and slope for a few minutes. Our data shows that the relationship between slope (%), relative speed (v) and relative HR is HR = 0.36 + 0.643 * v + 0.033 * s * v . HR behaved as predicted by a general equation of cost of locomotion in mammals and avians when it comes to the proportional impact of speed and slope, but not regarding the magnitude of such responses. This must reflect the loss of linearity between metabolic demand and HR at very high exercise intensities. Changes in HR could explain the behavior of most HRV estimators. However, one estimator (a1ApEn) could better be explained by changes in speed and slope. This indicates that HRV responds primarily to metabolic demand. The same general pattern of response of HRV to the different running conditions was observed in both groups, although, likely due to age-associated changes in cardiac control, how much a given HRV estimators changes differ between groups